38.4k views
5 votes
Solve for x.
-2(-x – 3) – 4x – 1= 13
Answer: 1
Submit Answer
Terms

2 Answers

0 votes

Answer:

x = -4

Explanation:

Expand

2x + 6 - 4x - 1 = 13

Rearrange, by collecting like terms and placing them on either side of the equation.

2x - 4x = 13 + 1 - 6

Simplify

-2x = 8

Divide both sides by -2

-2/-2x = 8/-2

x = -4

User HomerPlata
by
5.6k points
4 votes

Answer:

x=-3

Explanation:

-2(-x-3)-4x-1=13

2x+6-4x-1=13

-2x+5=13

-2x=8

x=-4

User Chris Miemiec
by
5.8k points